Catalytic Conversion of Glucose into 5-hydroxymethyl furfural over Spent Dry Batteries as Catalysts - Sami, Amenah; Ahmed, Muthanna (Iraqi Journal of Chemical and Petroleum Engineering, 2022)
Biomass is a popular renewable carbon source because it has a lot of potential as a substitute for scarce fossil fuels and has been used to make essential compounds like 5-hydroxymethylfurfural (HMF). One of the main components of biomass, glucose, has been extensively studied as a precursor for the production of HMF. Several efforts have been made to find efficient and repeatable procedures for the synthesis of HMF, a chemical platform used in the manufacturing of fuels and other high-value compounds. Sulfonated graphite (SG) was produced from spent dry batteries and utilized as a catalyst to convert glucose to 5-hydroxymethylfurfural (HMF). Temperature, reaction time, and catalyst loading were the variables studied. When dimethyl sulfoxide was utilized as the solvent at 180°C after 3 hours of reaction time, the greatest HMF yield, glucose conversion, and selectivity were attained, with 56.53 %, 97.5 %, and 57.979 %, respectively. This study demonstrates how to manufacture sulfonated graphite with increased catalytic activity for converting glucose to key biobased platform chemicals in a long-term sustainable manner.